Use of Online Public Access Catalogue in Guru Nanak Dev University Library, Amritsar: a Study - Kumar, Shiv; Vohra, Ranjana (Journal of Information and Knowledge, 2011)
The aim of the present study is to investigate the use of Online Public Access Catalogue by the users at Guru Nanak Dev University Library, Amritsar (Punjab). A sample of 112 users was taken from various categories of users covering different disciplines such as Basic Sciences, Applied Sciences, Social Sciences and Humanities. A questionnaire was designed and distributed among the users to collect the primary data. The paper focuses on various aspects of OPAC such as awareness, frequency of use, frequently used access points, satisfaction level, etc. The findings revealed that most of the users use the OPAC to locate the documents despite facing some difficulties. However, majority of the users are not satisfied with the OPAC. The study suggests that the users should be made familiar with the use and operation of the OPAC by providing special training.